THE INFLUENCE OF INDIVIDUAL AND SITUATIONAL FACTORS ON LOWER-LEVEL CIVIL SERVANTS’ WHISTLE-BLOWING INTENTION IN INDONESIA - Rijadh Djatu Winardi (Faculty of Economics and Business, Universitas Gadjah Mada, 2013)
The purpose of this research is to examine empirically the influence of individual andsituational factors on the whistle-blowing intentions among lower-level civil servants in Indonesia.This research proposes a conceptual model where individual and situational factors influencethe whistle-blowing intention among lower-level civil servants. More precisely this studyused three variables as individual factors based on the theory of planned behaviour (the attitudetoward whistle-blowing, the subjective norm, and the perceived behavioural control).Two vignettes were used to manipulate three situational factors (the seriousness of wrongdoing,the status of the wrongdoer, and the personal cost of reporting). A survey questionnaire wasdistributed to 106 civil servants from government institutions in Indonesia by using conveniencesampling. There are six hypotheses that were tested by using multiple regression analysis.This research found that individual and situational factors successfully predicted a whistleblowingintention. Specifically, research results indicate there are five antecedents of whistleblowingintention among lower-level civil servants in Indonesia labelled: the attitude towardwhistle-blowing, the subjective norm, the perceived behavioural control, the seriousness ofwrongdoing, and the status of the wrongdoer. Further implications for practice and researchare also discussed.Keywords: whistle-blowing intention, lower-level civil servants, theory of planned behaviour,individual factors, situational factors.